2021
DOI: 10.5812/jjm.118751
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Clinical Aspects of Diphtheria-Confirmed Cases from Capital City of Indonesia, Jakarta, and Surrounding Areas in 2017

Abstract: Background: The World Health Organization reported Indonesia as one of the countries with the most prevalent cases of diphtheria worldwide. The microbiological aspects of diphtheria-inducing bacteria are of great significance in tracing disease transmission and case management. However, clinical aspects are critical for updating clinical features and case management in the field, which may sometimes differ from theoretical foundations. Objectives: This study aimed to identify the microbiological and clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Unlike our previous study (13), we did not identify the NTTB strains to reduce the cost in this study because of the high cost of the PCR probe. Furthermore, previous studies documented that NTTB strains were never observed in diphtheria samples in Indonesia (4,10,13). The NTTB strain originated in Indonesia was isolated from the non-diphtheria sample (21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Unlike our previous study (13), we did not identify the NTTB strains to reduce the cost in this study because of the high cost of the PCR probe. Furthermore, previous studies documented that NTTB strains were never observed in diphtheria samples in Indonesia (4,10,13). The NTTB strain originated in Indonesia was isolated from the non-diphtheria sample (21).…”
Section: Discussionmentioning
confidence: 95%
“…Diphtheria is a serious health problem because of its high case fatality rate (CFR) (from about 10% to > 50% in severe cases) (3). Moreover, this disease is proved to spread across regions, islands, and even countries (4).…”
Section: Introductionmentioning
confidence: 99%